THE RISE OF CRYPTOCURRENCIES, BLOCKCHAIN NETWORK AND WHERE BITCOIN STANDS IN TODAY'S WORLD. - ŞEN, Erdal; ERGİN, Burak (Journal of International Social Research / Uluslararası Sosyal Araştırmalar Dergisi, 2019)
Bitcoin is a decentralized digital cryptocurrency that enables instant payments to anyone in the world. Bitcoins can be bought, sold and exchanged in other currencies. Bitcoin provides privacy and anonymity at an acceptable level. Bitcoin users can prove ownership of their operations on a bitcoin network with their secret keys and can spend their own value and transfer it to a new owner. Bitcoin uses peer-to-peer network to manage transactions. Payments are made in a few seconds. Every 10 minutes on average, a block of operations is validated by writing it on a global ledger called Blockchain. New blocks are added to global process ledgers by miners aiming for solving a particular math problem. A successful miner is rewarded with new bitcoins. The number of bitcoin in circulation can be calculated according to a curve that can be easily interpreted. According to a research, 21 million bitcoins will be produced by 2140. Currently, the total capitalization of the cryptocurrency market is over 14 billion dollars. While most governments have a positive attitude towards cryptocurrencies, they warn their citizens for the fact that there actually is no central authority behind Bitcoin and it cannot associated with any physical entity. The Blockchain has a wide range of uses, such as monitoring the ownership of documents, digital and physical assets, or voting, even if there is no Bitcoin.